Utilization Of Imagination-Based Plasticine Media In Improving Fine Motor Skills In Kindergarten - Faridah Andayani; Catur Nur Wijayanti (TEMATIK: Jurnal Pemikiran dan Penelitian Pendidikan Anak Usia Dini, 2022)
The purpose of the study was to determine efforts to improve students' fine motor skills through plasticine play activities. The research subjects of the students of TK Dharma Wanita Persatuan Pangkemiri Sidoarjo East Java, totaling 15 people. The focus of the study was fine motor and plasticine play activities. This study used a classroom action research approach with descriptive data analysis to display data using student observation sheets. The results of data analysis showed that plasticine play activities were able to improve children's fine motor skills. The improvement appears in the ability to form eye and hand coordination and the smoothness of the child's hands. The analysis data of the results showed an increase from cycle I with the completeness of learning outcomes of 23% with an average score of 1.80 to 40% of the totality of learning outcomes and the average score of students of 2.47 in cycle II and continued to increase in cycle III with the acquisition of completeness of learning outcomes reaching a maximum of 100% with an average score of students of 3.27.